Virtual Flipped Classroom: Solusi Alternatif Model Belajar di Tengah Pandemi - Ahmad hasani; Muhammad Thohir; Achmad Achmad (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
The Covid-19 disease outbreak has affected various lines of human life ranging from health, social, economic, and also political. The education aspect is one of the affected by this pandemic. Social distancing policy is one of the many obstacles in the world of education. This study aims to review Virtual Flipped Classroom more in-house. An expected learning model can be an alternative learning solution in the spreading epidemic. The type of research used by the author is library research with qualitative approach. The results of this conceptual research show that, VFC can be an ideal solution for learning. The use of ASA patterns (asynchronous synchronous+ asynchronous) is appropriate for schools that implement full virtual as distance learning (PJJ). For further researchers to be able to develop this Virtual Flipped Classroom learning model and test the effectiveness of this learning model based on their respective research locos because it can be an effective learning model solution in order to optimize the quality of education in the 4.0 era.